GREEN HUMAN RESOURCES MANAGEMENT TERHADAP KINERJA PERAWAT IGD DI RUMAH SAKIT UMUM SARI ASIH TANGERANG - Tekni Megaster; Fida Arumingtyas; Amelia Trisavinaningdiah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the Green Human Resources Management on the performance of ER Nurses. This study uses the associative method with a quantitative approach. The sample of this study was 70 respondents of emergency room nurses at Sari Asih General Hospital using a saturated sample. Primary data collection by distributing questionnaires. Multiple regression analysis technique using SPSS 25 software. The results showed partially that the Green Recruitment variable (X1) had a significant effect on Nurse Performance (Y). This is indicated by tcount > ttable (2.404 > 1.996), Green Training (X2) has a significant effect on Nurse Performance (Y). It is shown that tcount > ttable (3,077 > 1,996) and Green Compensation (X3) has a significant effect on the performance of Nurses (Y). This is indicated by tcount > ttable (5.333 > 1.996). And simultaneously Green Human Resources Management has a significant effect on Nurse Performance, namely Fcount > Ftable of (33.933 > 2.74). With a coefficient of determination of 58.90%, the rest were not examined in this study.